Mesenchymal stem cell therapy for equine tendinitis - Alves, Ana Liz Garcia [UNESP]; de Mattos Carvalho, Armando [UNESP]; Hussni, Carlos Alberto [UNESP] (Bentham Science Publishers, 2013)
Tendinitis is an important disease that leads to lameness and decreased performance in equine athletes and results in high costs associated with therapy due to a long recovery period and a high rate of recurrence. Although, several treatments for equine tendinitis have been described, few are effective in significantly improving the quality of the extracellular matrix and reducing the rate of recurrence. The use of cell therapy with mesenchymal stem cells (MSCs) derived from various sources has received much attention because of its therapeutic potential for equine tendinitis. In this paper, we review patents on stem cell therapy and the specific use of MSCs for the treatment of equine tendinitis. © 2013 Bentham Science Publishers.
Keywords: Adipose tissue; Adult stem cells; Bone marrow; Cell therapy; Equine; Tendinitis; 5' nucleotidase; bone morphogenetic protein 12; cell marker; endoglin; scatter factor; somatomedin C; Thy 1 antigen; vasculotropin; apoptosis; bone marrow biopsy; cell adhesion; cell proliferation; cell transdifferentiation; extracellular matrix; gene expression; hematopoietic stem cell; histopathology; horse; human; immunophenotyping; mesenchymal stem cell transplantation; multipotent stem cell; nonhuman; priority journal; recurrence risk; review; sarcoma; tendinitis; tissue engineering; wound healing